Biological approach in repair of partially inflamed dental pulp using second-generation platelet-rich fibrin and mineral trioxide aggregate as a pulp medicament in primary molars - Maria Manhas; Sudhir Mittal; A K Sharma; K K Gupta; V Pathania; V Thakur (Wolters Kluwer Medknow Publications, 2019)
Aim: The purpose of this study was to evaluate and compare clinically and radiographically PRF, MTA and Ca(OH)2 as a pulp dressing material in primary molars. Material and Methods: The study was conducted on 30 children between 6-9 years of age. Pulpotomy was performed using MTA(Gp I), PRF + MTA(Gp II) and PRF +Ca(OH)2(Group III). The teeth were evaluated clinically and radiographically after 1,3 and 6 months and were subjected to statistics analysis. Results: After 6 months follow-up the overall success rate was found to be highest in Gp I with success rate of 97% followed by Gp II 95% and Gp III 78.3%. The results were found to be statistically insignificant (P ≤ 0.05). Conclusion: All materials used in the present study were equally effective as the success rates are statistically insignificant.